Pengaruh Kualitas Informasi dan Online Customer Review terhadap Keputusan Pembelian pada Shopee Yasashi Japan Shop - Gunawan, Sarah; Kristanto, Rudi (Abiwara : Jurnal Vokasi Administrasi Bisnis, 2023)
This study aims to determine the effect of information quality and online customer reviews on purchasing decisions at Shopee Yasashi Japan Shop. The research method used was a quantitative method. The population in this study were Shopee Yasashi Japan Shop consumers. Sampling was done using probability sampling technique with random sampling method. The sample in this study consisted of 98 respondents who had bought products at Shopee Yasashi Japan Shop. Collecting data using a questionnaire. The collected data was scored and then analyzed using the SPSS (Statical Program for Social Science) 23.0 for Windows program. The results of this study indicate that Information Quality (X1) has a positive and significant influence on Purchase Decisions (Y) at Shopee Yasashi Japan Shop by 68%. Online Customer Review (X2) has a positive and significant influence on Purchase Decision (Y) at Shopee Yasashi Japan Shop by 51.4%. Information Quality (X1) and Online Customer Review (X2) have a positive and significant influence on Purchase Decision (Y) at Shopee Yasashi Japan Shop simultaneously on variable Y amounting to 84.5% and 15.5% influenced by other variables that not investigated by researchers in this study.